Microbial agents enhance the yield and quality of pears by regulating the composition and networks of microbial communities in the phyllosphere and rhizosphere - Luo, Na; Zhang, Yulou; Ren, Zhifeng; Wang, Xinfeng; Li, Hongbo; Zhang, Aiping (Frontiers in Microbiology, 2026)
Microbial management offers a sustainable pathway to enhance crop performance by optimizing plant-associated microbiomes. However, integrated strategies that concurrently target both the rhizosphere and phyllosphere to improve fruit tree productivity and quality remain underexplored. This study systematically evaluated the effects of combined soil and foliar microbial applications on the yield, fruit quality, and microbiome dynamics of ‘Yuluxiang’ pear. We compared conventional fertilization (CK) with two treatments: CK plus a soil-applied anti-replant disease agent (CF) and CK plus both the soil agent and a foliar growth-promoting inoculant (CFW). Microbial applications significantly increased the yield by up to 60.4% in CF treatment, and enhanced key fruit quality parameters, including soluble solids content (increased by 17.2% in CF and 16.7% in CFW) and fruit shape index. These agronomic improvements were closely associated with a targeted restructuring of bacterial communities in both the phyllosphere and rhizosphere. Specifically, beneficial phyla such as Actinomycetota were enriched in the phyllosphere under CFW treatment, while Bacillota increased in the rhizosphere under microbial amendments. Furthermore, co-occurrence network analysis revealed that microbial applications fostered more complex and cooperative microbial networks, with increased nodes and edges across both compartments. This work demonstrates that an integrated soil and foliar microbiome management strategy can mitigate replant disease constraints and elevate fruit quality, providing a practical approach for sustainable orchard production.